A high prevalence of extreme hyperferritinemia in acute hepatitis patients - Kazuhiro Kotoh (Dove Medical Press, 2009)
Kazuhiro Kotoh, Akihiro Ueda, Masatake Tanaka, Masayuki Miyazaki, Masaki Kato, Motoyuki Kohjima, Munechika Enjoji, Makoto Nakamuta, Ryoichi TakayanagiDepartment of Medicine and Bioregulatory Science, Graduate School of Medical Science, Kyushu University, Fukuoda, JapanAbstract: Although the mechanism underlying acute liver failure (ALF) has not been clarified, recent reports indicate overactivation of macrophages is involved in its progression. In diseases in which activated macrophages participate in the progression, elevated serum ferritin concentration counts among the characteristic laboratory findings. If activated macrophages play a key role in the development of ALF, serum ferritin levels might reflect the severity of acute liver injury. To confirm this, we evaluated the correlation between the serum ferritin concentration and other laboratory measurements in patients with acute hepatitis including ALF. One hundred consecutive patients with acute liver injury were enrolled, of whom 19 fulfilled the criteria for ALF. Serum ferritin concentrations correlated with serum alanine transferase activity as a whole. Interestingly, the correlation was strong in patients infected by hepatitis viruses, but weak in others. Although most patients with ALF had high levels of serum ferritin, not a few patients without ALF showed similar results. The serum ferritin level was generally increased in acute hepatitis patients, probably reflecting the degree of macrophage activation in the liver. Overactivation of macrophages appears to be essential, but not sufficient, for the development of ALF. Keywords: acute hepatitis, acute liver failure, ferritin, macrophage